Compassionate Resistance: An Ethic for Pastoral Care and Counseling - Ramsay, Nancy J. (The Journal of pastoral care, 1998)
Develops an ethic for ministries of care and counseling grounded in a scriptural and theological perspective which stresses the empowering love of God and the real possibilities of human love for one another. Argues that such a scriptural and theological framework holds special power in the recovery from child sexual abuse. Proposes and explicates the notion of “compassionate resistance” and how it can serve as a dynamic witness for sexual abuse survivors.